Development of a Sensor-Based Heartbeat and Body Temperature Monitoring System for Remote Chronic Patients - Obira, J. O.; Sinde, R. (Engineering, Technology & Applied Science Research, 2021)
The growing number of chronic diseases have stretched the healthcare sector. Globally, more than 36 million deaths per year are attributed to chronic disease complications. This has increased the demand for telemedicine in managing chronic patients as they must be on continuous monitoring for a long time. The involvement of wireless sensor networks and cloud computing technology in the health sector is increasing due to the potential it possesses in remote sensing and monitoring applications. This paper presents a developed system prototype for monitoring the heartbeat rate and body temperature of chronic patients using sensors. The monitored data are sent to a cloud database in real-time via an internet connection using the ESP8266 wireless module. The approach involves connecting a heart pulse sensor, an MLX90614 contactless temperature sensor, and the ESP8266 module to the Arduino development board. The goal of this work is to create a system that interfaces chronic patients and medical personnel in an attempt to avert the effects of insufficient health facilities, especially in rural Africa. The patient’s data in the cloud database can also be retrieved by medical personnel anytime in order to track the patient’s conditions and to advise the patient accordingly. The sensed heartbeat and body temperature readings were processed, sent, and recorded in the cloud database effectively.